Faktor Yang Mempengaruhi Keputusan Pembelian Pada Toko Sepatu Bata Palembang - Nicholas, Nicholas; Elizabeth, Sri Megawati (Universitas Multi Data Palembang, 2024)
The aim of this research is To partially and simultaneously analyze the influence of promotion and price on consumer purchasing decisions at the Bata Shoes Store in Palembang. The method used for data collection was by distributing questionnaires with a Likert scale, with a total of 373 respondents. The type of research used is descriptive. The sampling technique uses nonprobability sampling using a purposive sampling method with the help of SPSS 23 software, for Windows. The results of this research show that the partial test (t-test) of the promotion variables and price have a positive and significant effect on purchasing decisions. Simultaneous Test proves that the independent variables are promotion and price have an effect on the dependent variable, namely purchasing decisions.